Laporan ta hunan Proyek Pengembangan Kesejahteraan Anak Terlanter/ Panti Kary Taruna Nusa Tenggara Barat, tahun 1978-1979 (Kantor Wilayah Departemen Sosial, Propinsi Nusa Tenggara Barat, 1979)
Report of a project for the development of children and youth social welfare organizations in Nusa Tenggara Barat Province.